2015
DOI: 10.1038/srep14945
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Framework for Reservoir Computing and Extreme Learning Machines based on a Single Time-delayed Neuron

Abstract: In this paper we present a unified framework for extreme learning machines and reservoir computing (echo state networks), which can be physically implemented using a single nonlinear neuron subject to delayed feedback. The reservoir is built within the delay-line, employing a number of “virtual” neurons. These virtual neurons receive random projections from the input layer containing the information to be processed. One key advantage of this approach is that it can be implemented efficiently in hardware. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 21 publications
(44 reference statements)
4
87
0
Order By: Relevance
“…The proof of Section 4 shows a network is an ESN even if the largest eigenvalue of the recurrent connectivity matrix is equal to 1 and if the transfer function is either Equation (15) or (16). The proof is also extensible to other transfer functions.…”
Section: Summary Discussion and Outlookmentioning
confidence: 82%
See 1 more Smart Citation
“…The proof of Section 4 shows a network is an ESN even if the largest eigenvalue of the recurrent connectivity matrix is equal to 1 and if the transfer function is either Equation (15) or (16). The proof is also extensible to other transfer functions.…”
Section: Summary Discussion and Outlookmentioning
confidence: 82%
“…Single neuron reservoirs have been studied in other researches [15,16]. Here the intention is to illustrate the principle benefits and other features of critical ESNs.…”
Section: Examples Using a Single Neuron As A Reservoirmentioning
confidence: 99%
“…a reservoir without internal connectivity, in which the input layer is randomly mapped to the hidden layer [64]. In Ortín et al [57], it has been shown that the optoelectronic implementation of ELM yields comparable results to RC as long as past inputs are explicitly included in the input layer. A more powerful approach is that of implementing general machine learning models on a hardware device [65].…”
Section: Optoelectronic Delay-based Reservoir Computingmentioning
confidence: 98%
“…A number of classification, prediction, and system modelling tasks have been performed with state-of-the-art results. To name a few, excellent performance has been obtained for speech recognition [21,22,55], chaotic time series prediction [22,56,57], nonlinear channel equalization [21,[57][58][59], and radar signal forecasting [58,59]. A summary of the results obtained for each task is given in Table 1.…”
Section: Optoelectronic Delay-based Reservoir Computingmentioning
confidence: 99%
See 1 more Smart Citation